Effects of Verbal and Tactile Cues on Gluteal Force Production and Broad Jump Distance - BJ Lehecka; Terra Daniels; Bryson Koester; Wyatt Kropp; Matthew Reeves; Ryan Waterson (North American Sports Medicine Institute, 2024)
# Background Verbal and tactile cues can increase muscle activity, force production, and kinematics. Several studies demonstrate the effects of verbal and tactile cues on upper extremity muscles, while relatively few examined lower extremity muscles, specifically the gluteals. Studies that observed changes in gluteal function from verbal and tactile cues examined muscle activity via electromyography rather than force production or functional activities such as jumping. # Purpose The purpose of this study was to measure the effects of verbal and tactile cues on gluteal force production and broad jump distance. # Study Design Cross-Sectional cohort # Methods Gluteus maximus force production and broad jump distance were tested in forty-two healthy male and female university students at baseline and after verbal and tactile cues given in random order. Gluteus maximus force was measured using handheld dynamometry and reported in kilograms. Verbal cues included "push, push, push" before both tests. The examiner provided tactile cues to the gluteus maximus before force production testing, and the participant provided tactile cues to both gluteus maximus muscles before performing the broad jump. Performance on the broad jump was measured in centimeters. Descriptive statistics and test-retest reliability via Pearson correlation coefficients were calculated, differences in performance between sexes were analyzed with an independent t-test, and changes in force production and jump distance from baseline were analyzed using a one-way ANOVA. # Results Mean gluteus maximus force production following verbal cues significantly increased (p = 0.000) by 13.48% (3.83 kg) compared to the control condition, while gluteal force production following the tactile cues was not significantly different. Broad jump distance following the verbal cues significantly increased (p = 0.000) 3.99% (7.71 cm) compared to the control condition and significantly increased (p = 0.000) by 2.95% (5.71 cm) following the tactile cues. There were no significant differences in performances between males and females. The test-retest reliability of all measurements was 0.97-0.99. # Conclusion Verbal cues significantly increased gluteus maximus force production and broad jump distance. Tactile cues significantly increased broad jump distance but had no significant effect on gluteus maximus force. These results have implications for clinical testing and athletic performance when gluteus maximus force and jump distance are concerned. # Level of Evidence 3